Systematic Approach to Teaching English Nouns in The Context of Private English Course Classroom Instruction - Azwar Abidin (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
Vocabulary knowledge is a crucial component of successful language classroom instruction since all the main aspect of language teaching especially in second and foreign language classroom is depending on vocabulary mastery. In that case, the vocabulary instruction holds a crucial part that the teacher should pay a careful attention to make sure that the students learn the meanings of many words so they can communicate effectively and achieve academically. This research applied descriptive qualitative research to describe private English course instructors’ attitude toward teaching vocabulary through systematic approach and their students’ response. The researcher took notes while the classroom instruction took place and recorded the whole classroom interaction. By the end of the class, the researcher interviewed and transcribed their experience. The findings concluded that the instructors found this systematic approach was easy to implement and the students were engaged more in classroom activities. Over 75% of the students got excellent scores and they collected most of their points from the items which dealt with combining roots and affixes, identification of the meanings of those roots, and also identification of kinds of derived nouns whether it is personal (actor) or conceptual (action/ thing). Moreover, for about 85% of them have stated that the activities in the systematic approach in teaching English nouns were enjoyable.